Remote sensing in armed conflict studies: a bibliometric analysis - Maritza Yulieth Tangarife–Marulanda; Vladimir Henao–Céspedes (Institute of Advanced Engineering and Science, 2026)
This article addresses the potential use of remote sensing in conducting studies related to armed conflict. To carry out this approach, a bibliometric analysis was carried out, applying the preferred reporting items for systematic reviews and meta-analyses (PRISMA) methodology, through which we sought to identify the most relevant authors, the geographical distribution of productivity, and the research trends in the area. The analysis was carried out with information obtained from the Scopus reference database in August 2024. The results indicate that productivity growth began in the 2000s and is still under development. Additionally, the review of the articles indicated that the use of remote sensing in relation to armed conflicts has focused mainly on the study of the effects of armed conflict on land cover, environmental stability and, more recently, on the impact on agricultural areas from a food security perspective.